2020
DOI: 10.1016/j.scitotenv.2020.138399
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal trends of atmospheric Pb over the last century across inland China

Abstract: Sedimentary records from remote regions contain pollutants derived dominantly from atmospheric input, and thus have the potential to trace past atmospheric pollution history. Based on seventeen sediment records from relatively remote areas of China, atmospheric Pb pollution history during the last century was studied. These records suggest some slight pollution before ~1950 and display synchronous Pb enrichment processes since the 1950s, implying the start of widespread atmospheric Pb pollution in China. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 45 publications
(137 reference statements)
2
7
0
Order By: Relevance
“…The pollution and ecological risk status/difference of heavy metals between these lakes correspond well with the fact that lake KL received more anthropogenic pollutant emissions than other lakes as it is situated close to (~5 km) a small county (Guyuan) [ 25 ]. In contrast, the other four lakes (i.e., GH, MY, DL, and ZS) are situated relatively far from urban/industrial areas, and thus they receive fewer anthropogenic pollutant emissions [ 23 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The pollution and ecological risk status/difference of heavy metals between these lakes correspond well with the fact that lake KL received more anthropogenic pollutant emissions than other lakes as it is situated close to (~5 km) a small county (Guyuan) [ 25 ]. In contrast, the other four lakes (i.e., GH, MY, DL, and ZS) are situated relatively far from urban/industrial areas, and thus they receive fewer anthropogenic pollutant emissions [ 23 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Lakes GH and MY are sub-alpine lakes. They are situated on the remote Lvliang Mountain in Xinzhou City in central Shanxi Province [ 23 , 24 ]. Lakes DL and ZS lie at the north margin area of the E–W trending Hunshandake Desert Land on the southeastern Mongolian Plateau [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In China, numerous in‐depth studies on the characteristics of BC pollution have been carried out in dense urban agglomeration areas such as the North China Plain (NCP) region, the Yangtze River Delta (YRD) region, the Pearl River Delta (PRD) region, the Twain‐Hu Basin, and the Sichuan Basin (Chen, Zhao, et al, 2023; Lin et al, 2019; Pei et al, 2022; Wan et al, 2023; Wei et al, 2023; Yang et al, 2022; Yuan et al, 2022; Zhang et al, 2023; Zheng et al, 2022). Yang et al (2022) found that the refractory BC (rBC) core mass size distribution was bimodal, with a small secondary mode at ~687 nm in NCP.…”
Section: Introductionmentioning
confidence: 99%